A New Role for Browning as a Redox and Stress Adaptive Mechanism? - Jeanson, Yannick; Carrière, Audrey; Casteilla, Louis (Frontiers in Endocrinology, 2015)
The worldwide epidemic of obesity and metabolic disorders is focusing the attention of the scientific community on white adipose tissue and its biology. This tissue is characterized not only by its capability to change in size and shape but also by its heterogeneity and versatility. White adipose tissue can be converted into brown fat-like tissue according to different physiological and pathophysiological situations. The expression of uncoupling protein-1 in brown-like adipocytes changes their function from energy storage to energy dissipation. This plasticity, named browning, was recently rediscovered and convergent recent accounts, including in humans, have revived the idea of using these oxidative cells to fight against metabolic diseases. Furthermore, recent reports suggest that, beside the increased energy dissipation and thermogenesis that may have adverse effects in situations such as cancer-associated cachexia and massive burns, browning could be also considered as an adaptive stress response to high redox pressure and to major stress that could help to maintain tissue homeostasis and integrity. The aim of this review is to summarize the current knowledge concerning brown adipocytes and the browning process and also to explore unexpected putative role(s) for these cells. While it is important to find new browning inducers to limit energy stores and metabolic diseases, it also appears crucial to develop new browning inhibitors to limit adverse energy dissipation in wasting-associated syndromes.